Students' Perception of Using Perplexity Application in Writing Skills at English Department - Roisatul Hasanah; Ulfa Wulan Agustina; Nurul Nurul; Luluk Choirun Nisak Nur; Akhmad Kanzul Fikri (LPPM Universitas KH. A. Wahab Hasbullah, 2025)
This research aims to determine Unwaha students' perception of using the perplexity application in their writing skills. The respondents of this research were 24 students of English Department 5 term at KH. A. Wahab Hasbullah University, Jombang. The method used in this research is descriptive qualitative using triangulation in 3 stages, namely data reduction, data display, and conclusion. On the first day, students are introduced to the Perplexity application and asked to use Perplexity in learning writing skills. On the second day, students were asked to fill out questionnaires and interviews to collect data related to student perceptions through the Perplexity application in writing skills. The results of student responses stated that 74.8% of students responded well to the presence of perplexity in learning writing skills. This shows that perplexity has had a positive impact on students. Perplexity is considered a supporter in learning writing skills.